Role of Immuno-Inflammatory Cells Modified by Smoking in Periodontitis (Journal of Pharmaceutical Negative Results, 2022)
Periodontal disease is a chronic immuno-inflammatory disease resulting in the destruction of periodontal tissues. Oral biofilm with anaerobic microorganisms represents the main etiological factor for the occurrence of periodontal disease. However, the disease is influenced by several risk factors among which cigarette smoking is a major risk factor. The relationship between smoking and periodontal diseases has been studied broadly over the past 30 years. Cigarette smoke contains numerous toxic chemicals, which are known to have adverse effects on human cells and periodontal tissues. Chemicals found in cigarette smoke are also highly genotoxic and may lead to various forms of DNA damage. The initiation and progression of periodontal destruction result from the imbalance between the potentially pathogenic and intrinsic bacteria in dental plaque and the efficiency of the host’s defense. Nicotine appears to disrupt the integrity and function of periodontal tissues. Smokers present with higher proportion of sites with deeper probing depths and clinical attachment loss compared with nonsmokers. Smoking results in cellular damage and also acts as an immunosuppressor. Many of the substances in cigarette smoke causes cytogenetic damage, immunomodulatory effects, carcinogenic or addictive activity. Smoking has been identified as an important long-term predictor for tooth loss in patients treated for periodontitis, and, also appears to cause a stronger inflammatory reaction with an increased release of tissue destructive substances. Therefore, this article is designed to elaborate the role of immuno-inflammatory cells modified by smoking in periodontitis.